Drug Intake and Actinic Keratosis: A Case-Control Study - Andrea Sechi (Mattioli1885, 2021)
Background: Actinic keratosis (AK) is a form of premalignant keratinocyte dysplasia. Recently, the role of photosensitizing drugs in the development of AK has been postulated.